Compilation Report Finance with Implementing EMKM SAK to Palapa Penyet Grilled Chicken MSME in Tanjung Gusta Village - Hasbiyana Haudi Nasution; Renny Maisyarah; An Suci Azzahra (International Forum of Researchers and Lecturers, 2025)
Research This aim For compile report financial situation of Palapa Grilled Chicken MSME with apply Standard Accountancy Finance Entity Micro, Small, and Medium Enterprises (SAK EMKM). This MSME located in Tanjung Gusta Village and has operate since in 2012, however recording his finances Still done manually and not yet in accordance with standard applicable accounting. This is cause owner business difficulty in understand condition finance business in a way accurate. The method used in study This is method descriptive qualitative with technique data collection in the form of observation, interviews, and documentation. The data collected Then analyzed and compiled in form report finances consisting of from report position finance, reports profit loss, and notes on report finance in accordance with provisions of the EMKM SAK. Research results show that compilation report finance based on SAK EMKM can helping MSMEs to obtain a clearer picture clear about report position financial reports profit loss and performance business in a way overall. The implementation of SAK EMKM also increases awareness owner business to importance recording systematic and accurate financial research.​ This expected can become references and guides for other MSME actors in increase quality management finance through implementation standard simple, relevant, and easy accounting understood.